Why Are You Learning Japanese? Vietnamese University Students' Perspectives on Work and Life between Vietnam and Japan. Issue 4 (2nd October 2022) - Hashimoto, Kayoko
ABSTRACT: Although the numbers of Vietnamese skilled workers and students in Japan have been increasing rapidly, this phenomenon has not been fully understood in relation to Japanese language teaching in Vietnam's higher education. In 2008, the Vietnamese government announced its so-called Project 2020 to enhance foreign language capacity within the Association of Southeast Asian Nations (ASEAN), coinciding with ASEAN's 2009 decision to adopt English as its sole working language. Project 2020 has promoted a second foreign language, Japanese, reflecting Vietnam's pro-Japan policy and Japan's business interests in Vietnam. The heavy reliance on support from the Japanese government and industry, however, has created problems in delivering a curriculum suited to the local context. Based on survey and interview data from university students and teachers in Japanese programmes in Vietnamese universities, this article argues that although students' learning experiences have been shaped by the university curriculum, including industry internships and study abroad, individual learners believed that 'cultural differences' could prevent them from living in Japan in the long term. They were not studying Japanese to satisfy their future Japanese employers or exclusively for monetary reward, but for their personal growth as skilled workers who could contribute to the further development of Vietnam.